ЭКОНОМИКА И ЭКОЛОГИЯ: УПРАВЛЕНИЕ ЭКОЛОГО-ЭКОНОМИЧЕСКИМИ СИСТЕМАМИ В УСЛОВИЯХ УСТОЙЧИВОГО РАЗВИТИЯ - Рахимова, С А (Journal of Economic Research & Business Administration, 2015)
In given article the basic components of stable development is considered: the economical and ecological. It is interrelationship and interinfluence is showed. The necessity of ecological –economical management, basic tools is considered. The model of ecological-economical management system is proposed.